2022
DOI: 10.1038/s41467-021-27921-1
|View full text |Cite
|
Sign up to set email alerts
|

MAPK4 promotes triple negative breast cancer growth and reduces tumor sensitivity to PI3K blockade

Abstract: About 15–20% of breast cancer (BCa) is triple-negative BCa (TNBC), a devastating disease with limited therapeutic options. Aberrations in the PI3K/PTEN signaling pathway are common in TNBC. However, the therapeutic impact of PI3K inhibitors in TNBC has been limited and the mechanism(s) underlying this lack of efficacy remain elusive. Here, we demonstrate that a large subset of TNBC expresses significant levels of MAPK4, and this expression is critical for driving AKT activation independent of PI3K and promotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 31 publications
(37 reference statements)
1
33
1
Order By: Relevance
“…Compared to ERK3, which is expressed in most tissues and cell lines, ERK4 shows a more restricted expression profile and is generally found at low or undetectable levels in most cell lines. Previous independent observations from our laboratories suggested that ERK4 is not expressed in some of the MAPK4-high cell lines described in Wang et al 4 paper, prompting us to examine in more detail the expression of ERK4 in their cell line panel. We first measured the abundance of MAPK4 mRNA by quantitative RT-PCR.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Compared to ERK3, which is expressed in most tissues and cell lines, ERK4 shows a more restricted expression profile and is generally found at low or undetectable levels in most cell lines. Previous independent observations from our laboratories suggested that ERK4 is not expressed in some of the MAPK4-high cell lines described in Wang et al 4 paper, prompting us to examine in more detail the expression of ERK4 in their cell line panel. We first measured the abundance of MAPK4 mRNA by quantitative RT-PCR.…”
Section: Resultsmentioning
confidence: 92%
“…To investigate the role of ERK4 in TNBC, Wang et al 4 first surveyed a panel of TNBC cell lines and found that ERK4 is highly expressed in MDA-MB-231, Hs578T and HCC1937 cell lines (referred to as MAPK4-high), while other TNBC cell lines express low-to-undetectable levels of the kinase. They used the NSCLC cell line H1299 as a positive control of ERK4 expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations